Character Education Through Example Values K.H. Mas Mansur in Learning History - Janah, Siti Raodatul; Pajriah, Sri; Suryana, Aan; Firdaus, Dede Wahyu (Universitas Negeri Padang, 2024)
Character education refers to school efforts to shape, guide, and develop student behavior according to specific standards. This research aims to analyze the biography and example of KH Mas Mansur and the cultivation of character education through the exemplary values of K.H. Mas Mansur in learning history in class XI IPS 1 MAN 1 Darussalam Ciamis. This research uses a qualitative research method and a case study design. The data collection techniques used were observation, interviews, and documentation. The research results show that (1) K.H. Mas Mansur was born in Surabaya on June 25, 1896. He is known as a young man who is diligent and trustworthy, always speaks well, and has extensive knowledge. K.H. Mas Mansur has been a leader in many institutions, such as Chairman of the Surabaya Branch of Muhammadiyah for two terms and Chairman of the Tarjih Council. (2) The exemplary values of K.H. Mas Mansur, which can be applied in history learning in class XI IPS 1 MAN 1 Darussalam Ciamis, namely religious values, discipline, curiosity, nationalism, patriotism, respect for achievement, friendly and communication, like to read, and a sense of responsibility, (3) Instilling character education through the exemplary values of K.H. Mas Mansur has been successfully implemented quite well and has had a positive impact on history learning in class XI IPS 1 starting from planning, implementation, to the evaluation stage.